Early combination versus initial metformin monotherapy in the management of newly diagnosed type 2 diabetes: An East Asian perspective. Issue 1 (9th November 2020) - Ji, Linong; Chan, Juliana C. N.; Yu, Miao; Yoon, Kun Ho; Kim, Sin Gon; Choi, Sung Hee; Huang, Chien‐Ning; Te Tu, Shih; Wang, Chih‐Yuan; Paldánius, Päivi Maria; Sheu, Wayne H. H.
Abstract: Type 2 diabetes (T2D) in the East Asian population is characterized by phenotypes such as low body mass index, an index of β‐cell dysfunction, and higher percentage of body fat, an index of insulin resistance. These phenotypes/pathologies may predispose people to early onset of diabetes with increased risk of stroke and renal disease. Less than 50% of patients with T2D in East Asia achieve glycaemic targets recommended by national or regional guidelines, which may be attributable to knowledge and/or implementation gaps. Herein, we review the latest evidence with special reference to East Asian patients with T2D and present arguments for the need to use early combination therapy to intensify glycaemic control. This strategy is supported by the 5‐year worldwide VERIFY study, which reported better glycaemic durability in newly diagnosed patients with T2D with a mean HbA1c of 6.9% treated with early combination therapy of vildagliptin plus metformin versus those treated with initial metformin monotherapy followed by addition of vildagliptin only with worsening glycaemic control. This paradigm shift of early intensified treatment is now recommended by the American Diabetes Association and the European Association for the Study of Diabetes. In order to translate these evidence to practice, increased awareness and strengthening of the healthcare system are needed to diagnose and manage patients with T2D early for combination therapy.